Mendelian randomization analysis reveals no causal relationship between thyroid function and sarcopenia-related traits - Xu, Rui; Li, Yan-Yan; Xu, Hong (Frontiers in Endocrinology, 2024)
Background：Recent research has indicated a potential association between thyroid function and sarcopenia, but the specific mechanisms and a definitive causal relationship have yet to be established. Therefore, the objective of this study is to examine the potential causal connection between thyroid function and sarcopenia-related traits, including hand-grip strength, appendicular lean mass (ALM), and walking pace.Methods：The study used a bi-directional two-sample MR design, with thyroid function examined as the exposure and sarcopenia-related traits as the outcome in the first stage, and then reversed in the second stage. The genetic instruments for thyroid function were obtained from a comprehensive meta-analysis involving 271,040 participants. Data on sarcopeniarelated traits based on GWASs were collected from the UK Biobank, which includes up to 461,026 European participants. The estimates for MR were calculated using the inversevariance weighted (IVW) method, and several sensitivity analyses were performed.Results: After applying the Bonferroni correction for multiple testing, our MR analyses revealed no significant impact of thyroid function liability on sarcopenia-related traits.Similarly, our reverse MR analysis did not provide evidence supporting the influence of liability to sarcopenia-related traits on thyroid function. The results of the primary IVW MR analyses were largely in line with those obtained from our sensitivity MR analyses.Our research findings do not suggest a link between thyroid function and sarcopenia-related traits. The associations identified in epidemiological studies may be influenced, at least in part, by shared biological mechanisms or environmental confounders.